Penerapan Konsep Konsolidasi Tanah pada Permukiman Kumuh Kawasan Semanggi Kota Surakarta Berdasarkan Peraturan Kepala Badan Pertanahan Nasional Nomor 12 Tahun 2019 - Yunitya Hilda Natasya; Rahayu Subekti; Purwono Sungkowo Raharjo (Amal Insani Foundation, 2023)
This research aims to describe and analyze the implementation of land consolidation arrangements for slum settlements and the obstacles that arise related to land consolidation arrangements for slum settlements in the Semanggi area of Surakarta City. This research is using an empirical methodology with descriptive features. Both primary and secondary sources of information are used in this study; primary sources included interviews, while secondary ones included literature reviews. The location of this research lies in the housing service, residential area, and the mainland of Surakarta. The 1945 Constitution of the Republic of Indonesia (UUD 1945) guarantees all Indonesian residents the right to live in a decent home. This constitutional law gives the government significant influence over the production of any slums-related policies. The result of this study indicates that land consolidation arrangements for slum settlements in the Semanggi area have not been fully implemented in accordance with the applicable laws and regulations, including inadequate fulfillment of PSUs such as the lack of hydrants (fire protection), gas networks, telephone networks, and cemeteries in all setting areas. Obstacles in the arrangement of land consolidation include obstacles in implementation and obstacles in regulations. Obstacles in implementation lead to development delays due to non-fulfillment of the requirements for land consolidation participants and overlapping housing and PSU construction. Obstacles to regulations occur due to a discrepancy in the arrangement pattern between the arrangement on the ground and Government Regulation Number 14 in 2016 concerning Implementation of Housing and Residential Areas.